STRATEGI PEMBERDAYAAN MASYARAKAT DESA MELALUI PENGEMBANGAN EKONOMI LOKAL DI KABUPATEN HALMAHERA BARAT PROVINSI MALUKU UTARA - Ayler Beniah Ndraha; Dedy Pribadi Uang (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2018)
West Halmahera Regency is a district in one of the Provinces in North Maluku. The strategy of empowering rural communities through the development of local economies in Halmahera Regency, North Maluku Province needs to be formulated because of the magnitude of the potential of this region. It is unfortunate that the attention of the government and the private sector has not touched the program because it is able to create new business fields that can bring local revenue West Halmahera Regency and income for independent and participant communities. The background of this problem is the basis of the authors to examine the strategy of empowering rural communities through local economic development in the western Halmahera district of North Maluku Province with a qualitative method of descriptive research method. The results of the community empowerment strategy in developing the local economy state that there needs to be sectoral synchronization that consists of the government, the private sector and the community. Several factors that have not supported the community empowerment strategy in developing the local economy in West Halmahera Regency are communication factors, regional potential mapping, human resources, infrastructure, and monitoring and evaluation. Keywords: empowerment strategy, village, local economy.